2005
DOI: 10.1007/s00383-005-1404-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent yolk sac tumor following resection of a neonatal immature gastric teratoma

Abstract: Gastric teratomas are very rare and usually benign. Only a few cases of gastric teratomas with malignant components have been reported. This report describes recurrence of a yolk sac tumor following resection of a neonatal immature gastric teratoma. Gastric teratoma recurring as a malignant lesion has not been previously reported. Recurrence of immature gastric teratomas should be considered, and a periodic follow-up check with alpha-fetoprotein level should be mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
(18 reference statements)
0
28
1
Order By: Relevance
“…In fact, intracranial teratoma with fetiform remains of multiple individuals, as presented in Ruysch's case, has been reported only twice [Kimmel et al, 1950; Naudin ten Cate et al, 1995]. Gastric teratoma (case 3) accounts for less than 1% of all teratomas in childhood [Cairo et al, 1981] with a 161 reported cases [Ukiyama et al, 2005]. Only five cases concern adult individuals [Gray et al, 1964; Liu et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, intracranial teratoma with fetiform remains of multiple individuals, as presented in Ruysch's case, has been reported only twice [Kimmel et al, 1950; Naudin ten Cate et al, 1995]. Gastric teratoma (case 3) accounts for less than 1% of all teratomas in childhood [Cairo et al, 1981] with a 161 reported cases [Ukiyama et al, 2005]. Only five cases concern adult individuals [Gray et al, 1964; Liu et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Balik et al (1990) reported the second case of malignant gastric teratoma in an infant that was also treated by total excision. Ukiyama et al (2005) on the other hand reported a recurrent yolk sac tumor following resection of a neonatal immature gastric teratoma. This calls for a close follow-up of all patients with immature gastric teratoma.…”
Section: Discussionmentioning
confidence: 99%
“…1 These tumors usually present as exophytic masses with symptoms of obstruction and upper gastrointestinal bleeding. 2,3 The clinical symptoms combined with the CT scan images usually allow for a reasonably definite pre-operative diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Tumor localization with calcium gluconate arterial stimulation with hepatic venous sampling (ASVS) for insulin has been shown in cases of unsatisfactory imaging or suspected tumors smaller than 1cm. The surgeon's goal is to cure the patient with minimal morbidity, and confidence in localization of the lesion is a means to this end.…”
Section: Introductionmentioning
confidence: 99%